Fase de intervención urbano - paisajística para la articulación del borde urbano deteriorado de la cabecera municipal de Candelaria con el río Párraga. (2024)
The development of architecture in the territories has been too transcendental that it continues to progress at levels beyond architectural elements, positioning itself in society as an important branch in the social, cultural, economic fields, among others of daily life, specifically in the functioning of an urbanization.